About Betty's boob - Cazot, Véronique (Archaia, 2018)
"She lost her left breast, her job, and her guy. She does not know it yet, but this is the best day of her life. An inspiring and surprisingly comedic tale of loss and acceptance told largely through silent sequential narrative"--Back cover.